Formação dos sujeitos participantes de uma atividade de comunicação sobre as questões sociocientíficas dos agrotóxicos - Añez, Fernanda (Universidade Federal de São Carlos, 2020)
The lack of understanding about some everyday events involving science and technology can have repercussions for the social life of all of us, as our participation in political decisions or understanding of the world and its scientifictechnological development becomes limited. Limitations in social responsibility actions can be considered as resulting from the dehumanization process of the individuals. Moreover, we must remember that science, as human production, is not free of values, and its development can have future impacts on society and the world. In the search for a way to overcome this process, science education committed to the development of critical awareness, shows the fundamental formation of individuals, as it enables understanding and critical positioning in front of the impacts of technological development on society. To develop scientific training for social responsibility and critical positioning regarding the impacts of scientific-technological development, our research sought to understand what are the potentials of an extension activity based on the socio-scientific issues of pesticides, in the scientific and critical training of participants. When talking about the extension, considered part of the university tripod, we believe in its articulating role that through communication and dialogue, educator and student get educated in communion. Thus, in the context of the extension activity, based on communication, proposed at UFSCar, campus Araras, we constituted our data based on the theoretical-methodological references of the participating research. The records were made through recordings of the activities performed and later transcribed, and provided us with data to interpret according to designated a priori and a posteriori categories based on Content Analysis. Data analysis allowed us to conclude, discuss discussions about the intentionality of S&T development, about the University and its role in the training of professionals, about the extensions of universal extension and the possibilities of communication between the University and the community, among other topics, there is a formation of individuals. Science teaching through the SSI is a way to scientifically educate students, who end up with problems in the world, develop critical awareness, and engage in the search for social justice and public participation in issues involving scientific and technological knowledge.
Formation of individuals participating in communication activity about the socio-scientific issues of pesticides
Keywords: Extensão universitária; Dialogicidade; Agrotóxicos; CTS; Questão sociocientífica; Educação científica; University extension; Dialogicity; Pesticides; STS; Socio-scientific issue; Science education; CIENCIAS HUMANAS::EDUCACAO::ENSINO-APRENDIZAGEM